Perubahan Pengaturan Tindak Pidana Pendanaan Terorisme Dalam Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Ajie, Bintang Wicaksono (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2024)
Criminal Acts of Terrorism (CAT) are a global threat that threatens national security as well as regional and global peace and stability, including Indonesia. Terrorism financing is one of the key factors that enable terrorist groups to carry out acts of terrorism in Indonesia. Therefore, efforts to prevent and eradicate the Criminal Act of Terrorism Financing (CATF) are very important to stop the CAT. In its development, CATF can be seen as a criminal act that stands alone and is different from its parent crime, terrorism. This is because terrorism financing has peculiarities as well as different modus operandi. Therefore, the international community includes it in the anti-money laundering and terrorism financing regime. In response to this, Indonesia has separated CATF from CAT through Law Number 9 of 2013 concerning the Prevention and Eradication of CATF. Over time, the Government of Indonesia has ratified and enacted the Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code (CC), which also regulates CATF. This research uses normative legal research methods through document review. This study analyzes the different arrangements of the CATF after enacting the new Criminal Code Law. Differences in the regulation of the CATF after the enactment of the new Criminal Code include the CATF being part of the terrorism criminal act regime and removing the phrase "intentionally" in CATF-related offenses, a decrease in the threat of criminal fines for CATF.